Factors Affecting Entrepreneurial Intention: a Study of Secondary Technical-Professional Education Students in Chile - Jorge Antonio Torres-Ortega (Revista Escuela de Administracion de Negocios, 2022)
Entrepreneurial intention is often considered the key determinant of business creation and the development of entrepreneurial behavior. To date, most studies on the determinants of entrepreneurial intention have collected data from undergraduate or graduate university students. In contrast, the present study addresses this issue at the secondary education level. The primary objective is to test students’ entrepreneurial intention between 16 and 18 years in Chile’s Secondary Technical-Professional Education programs. For this purpose, we applied a survey to a sample of 2373 students attending four different Technical-Professional Education Centres located in three different regions of this country. Based on the Entrepreneurial Potential Model, we tested the influence of perceived feasibility, perceived desirability, and propensity to act on students’ entrepreneurial intention. Applying a well-fitted logistic regression model shows that students with moderate risk propensity are more likely to show entrepreneurial intention. Furthermore, the study observed no association between perceived feasibility nor perceived desirability of a business venture with students’ entrepreneurial intention; nor was a relationship found between the propensity to act and students’ entrepreneurial intention.